The factors affecting the intention to purchase halal Fast-Moving Consumer Goods (FMCG) among Muslim staff consumers in Felda Global Ventures Plantations Malaysia Sdn Bhd (FGVPMSB) / Nur Liana Latif and Nurul Farisya Zainol - Latif, Nur Liana; Zainol, Nurul Farisya (Faculty of Business and Management, 2016)
This research explores the factors affecting the intention to purchase Halal fast-moving consumer goods (FMCG) among Muslim staff consumers in Felda Global Ventures Plantations Malaysia Sdn Bhd (FGVPMSB). A survey of the intention to purchase Halal fast-moving consumer goods (FMCG) was conducted to determine the factors that affect the intention to purchase Halal FMCG between Halal certification, personal societal perception and religious belief Felda Global Ventures Plantations Malaysia Sdn Bhd Kuala Lumpur. A total of 100 usable questionnaires were distributed and 82 were returned. The findings shows that the three (3) variables which are Halal certification, personal societal perception and religious belief were important in determining the factors affecting the intention to purchase Halal fast-moving consumer goods (FMCG), therefore, Felda Global Ventures Plantations Malaysia Sdn Bhd in Kuala Lumpur need to consider these factors and provide the best way to improve the intention to purchase Halal fast-moving consumer goods (FMCG).